2015
DOI: 10.1007/s10237-015-0660-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale impact of nucleotides and cations on the conformational equilibrium, elasticity and rheology of actin filaments and crosslinked networks

Abstract: Cells are able to respond to mechanical forces and deformations. The actin cytoskeleton, a highly dynamic scaffolding structure, plays an important role in cell mechano-sensing. Thus, understanding rheological behaviors of the actin cytoskeleton is critical for delineating mechanical behaviors of cells. The actin cytoskeleton consists of interconnected actin filaments (F-actin) that form via self-assembly of actin monomers. It has been shown that molecular changes of the monomer subunits impact the rigidity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 92 publications
2
34
0
Order By: Relevance
“…We found that during the transition from a network into a bundle, actin filaments undergo buckling and reorientation in various ways, and a large portion of tension is built during the structural reorganization rather than after bundle formation. In addition, we incorporated systematic variations of initial filament orientation that have not been included in our previous studies [13, 16, 2427], motivated by observation that transverse arcs located at the interface between lamellipodia and lamella are formed by compaction and realignment of actin filaments with biased orientations within the lamellipodia [28]. …”
Section: Discussionmentioning
confidence: 99%
“…We found that during the transition from a network into a bundle, actin filaments undergo buckling and reorientation in various ways, and a large portion of tension is built during the structural reorganization rather than after bundle formation. In addition, we incorporated systematic variations of initial filament orientation that have not been included in our previous studies [13, 16, 2427], motivated by observation that transverse arcs located at the interface between lamellipodia and lamella are formed by compaction and realignment of actin filaments with biased orientations within the lamellipodia [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of experimental studies focused on the AXH domain, a similar effort has not been put on the side of molecular modelling to investigate structural and dynamics of ATH m till now. However, molecular modeling, and in particular molecular dynamics has been widely demonstrated to provide important or even exceptional insights to better understand molecular mechanisms at the basis of subcellular phenomena, such as the ones that drive protein aggregation and protein misfolding in neurodegenerative diseases …”
Section: Introductionmentioning
confidence: 99%
“…However in modeling studies only one types of nucleotide is considered. For example, in Table 2, Li et al (2013) andBidone et al (2015) used ADP actin which is same as this study. Moreover, in Table 3, the nucleotide of Li et al (2014) is ADP and in torsional rigidity evaluation, Yasuda, Miyata, and Kinosita (1996) used ATP-AF.…”
Section: Torsional Rigiditymentioning
confidence: 99%
“…Moreover, a number of previous studies focused on computer modeling of nanomechanical properties of AF. These studies can be classified base on the used method into three major groups namely, molecular dynamics (MD) simulations (Splettstoesser, Holmes, No e, & Smith, 2010Ghodsi & Kazemi, 2012), multiscale modeling (Fan, Saunders, & Voth, 2012;Deriu et al, 2011;Bidone, Kim, Deriu, Morbiducci, & Kamm, 2015;Deriu et al, 2012), and continuum mechanics modeling. All-Atoms (AA) MD simulation is used to investigate the structural modeling of F-actin (Splettstoesser et al, 2010(Splettstoesser et al, , 2011.…”
mentioning
confidence: 99%